Extracellular Vesicles from Stem and Progenitor Cells for Cell-Free Regenerative Therapy - Haque, Nazmul; Widera, Darius; Govindasamy, Vijayendran; Soesilawati, Pratiwi; Abu Kasim, Noor H. (Current Molecular Medicine, 2022)
Cell-based regenerative therapies involving stem or progenitor cells are considered as possible therapeutic modalities to treat non-communicable and degenerative diseases. Recently, regenerative outcomes of cell-based therapies have been linked to paracrine factors and extracellular vesicles [EVs] released by the transplanted cells rather than the transplanted cells themselves. EVs contain a cargo that includes microRNAs [miRNAs], mRNAs, as well as proteins. Their role in mediating intercellular communication has been acknowledged in several studies. However, the regenerative potential of the miRNAs, mRNAs, and proteins that are present in EVs is a matter of ongoing scientific debate. In this review, we discuss EVs as an alternative to stem cell-based therapy to treat some of the non-communicable and degenerative diseases. Moreover, we also propose that pre-treatment of the cells could help to produce EVs enriched with particular miRNAs, mRNAs, and/or proteins that could support the successful regeneration of a targeted organ
Keywords: paracrine factor